An Analysis of the 2019’s National Physics Exam Questions Using the Taxonomy of Introductory Physics Problem - Muhammad Qaddafi; Muh. Syihab Ikbal; Rahmi Indah Sari (Department of Physics Education, Universitas Mataram, 2022)
The study aims at describing the composition of the cognitive system within the national exams of high school physics questions in 2019. The theoretical framework applied in analysing the exam refers to Taxonomy of Introductory Physics Problem (TIPP). Then, this study applies a quantitative descriptive design by conducting document analysis towards the aforementioned exam, which consists of 40 item questions. Interestingly, the findings indicate that the analysed questions have be designed based on the TIPP principles, referring to the categories of remembering, understanding, analysing, and utilising knowledge with 3, 2, 15, and 20 questions respectively. It indicates that the questions for each category are not evenly distributed as the categories of remembering and understanding have lower number questions compared to others. Such evidence could truly become essential insights for the national exam question development team to consider the portion comparison of the question items for the four categories within TIPP.